(3LgO Gdebd hLgO GdeSJOds - (3aGQGHj, YeQ Hf Gdbhe, GdTgjQ HGdfXGes; (3eMeO Hf CMeO Hf eMeO GdbQTj GdCHjhQOj , CHh GdeXaQ,J (B507 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3agPg hQbGJ JTJed Ydi aSQ eG GSJHge, hTQM eG GSJYLe ef cJGH GdfLOjGJ hhSeJg HLgO Gdebd hLgO GdeSJOd s
(3BNQgG (B:s
(3eDdag YeQ Hf GdbhGe jYQag UMHg HGdfXGe JjSQ aj YGe OaM Jhdi dgLQI gGOj gOGI GdCfGe Ydjg ef Gddg CRci GdUdGI hddBd hGdUMH CUai SdGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B178s
(3GdfLOjGJs
(3aj GdbUGFO GdYLjHI GdeSeGI HOjhGf GdCHjhQOis
(3HgG fbhd hELGRGJ hef gPg Gdfbhd fSNI cJGH LHQjd Hf HNJjThY Edi GdeJhcd ef hQbI (B178-182s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs